The constitution of arbitration / Victor Ferreres Comella, Universitat Pompeu Fabra. - Ferreres Comella, Víctor (Comparative constitutional law and policy., 2021)
This work is the first systematic discussion of arbitration from a constitutional perspective, covering the most important types of arbitration, including domestic arbitration in private law, international commercial arbitration, investment treaty arbitration, and state-to-state arbitration. Victor Ferreres Comella argues for the recognition of a constitutional right to arbitration in the private sphere and discusses the constraints that the state is entitled to place on this right. He also explores the conditions under which investment treaty arbitration is constitutionally legitimate, and highlights the shortcomings of international adjudication from a constitutional perspective. The rich landscape of arbitration is explained in clear language, avoiding unnecessary technical jargon. Using examples drawn from a wide variety of domains, Ferreres bridges the gap between constitutional and arbitral theory.